Cognitive Justice in Islamic Education: Decolonizing Pedagogical Practices through Tarbawi Tafsir of QS. Al-Alaq: 1-5 - Mahdiyin, Khizbullah Al; Tholchah, Moch. (Fakultas Tarbiyah - Universitas Nahdlatul Ulama Sunan Giri, 2025)
This study examines the role of tafsir tarbawi in the epistemic decolonization of Islamic education through a critical analysis of QS. Al-‘Alaq: 1–5. The objective of this research is to deconstruct the colonization of knowledge systems rooted in modern educational paradigms and to accommodate cognitive justice by integrating Qur’anic values, local wisdom, and contemporary scientific knowledge, using QS. Al-‘Alaq: 1–5 as the analytical framework. Employing a qualitative approach with critical discourse analysis, this study explores classical and contemporary tafsir texts as well as academic literature to uncover the deeper meanings of these verses in relation to the decolonization of Islamic educational epistemology. The findings reveal that the verses of QS. Al-‘Alaq: 1–5 serve not only as a call to literacy but also as an imperative to critically examine and reflect on reality through a holistic tawhid-based lens. The study indicates that the tafsir tarbawi approach effectively challenges the dominance of Western epistemology and offers opportunities for curriculum reform and pedagogical methods that are more inclusive, interdisciplinary, and grounded in cognitive justice. The implications of this research support the development of optimized educational strategies through the use of information technology, educator training, and cross-disciplinary collaboration to establish an Islamic education system that is independent, just, and responsive to global challenges.